2005
DOI: 10.1051/rnd:2005001
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and neuropsychiatric disorders

Abstract: -Epidemiological evidence suggests that dietary consumption of the long chain omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), commonly found in fish or fish oil, may modify the risk for certain neuropsychiatric disorders. As evidence, decreased blood levels of omega-3 fatty acids have been associated with several neuropsychiatric conditions, including Attention Deficit (Hyperactivity) Disorder, Alzheimer's Disease, Schizophrenia and Depression. Supplementation studies, using ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(146 citation statements)
references
References 243 publications
(235 reference statements)
1
139
1
5
Order By: Relevance
“…Moreover, it is uncertain as to what extent diet in childhood is related to ADHD symptoms. 24 It is also possible that differential postnatal upbringing by obese women could be related to increased risk of ADHD. However, we find this unlikely and have no data to indicate that obese women are less likely to care their children.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Moreover, it is uncertain as to what extent diet in childhood is related to ADHD symptoms. 24 It is also possible that differential postnatal upbringing by obese women could be related to increased risk of ADHD. However, we find this unlikely and have no data to indicate that obese women are less likely to care their children.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Evidence has been mounting indicating that deficient intakes of n-3 PUFAs could play a role in the pathophysiology of a wide range of psychiatric disorders that have included (but are not limited to) mood disorders, schizophrenia , attention deficit and hyperactivity disorders, Alzheimer disease and dementias (Alessandri et al, 2004;Freeman et al, 2006;Young et al, 2005). This evidence has been based in part on international comparison studies of associations between seafood consumption and the prevalence of some psychiatric disorders (Hibbeln, 1998;Hibbeln, 2002;Noaghiul and Hibbeln, 2003) and on cross-sectional, case control or cohort studies investigating associations between these disorders and fish or n-3 polyunsaturated fatty acids (PUFAs) intake or tissue PUFAs concentrations (Alessandri et al, 2004;Freeman et al, 2006;Young et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence has been based in part on international comparison studies of associations between seafood consumption and the prevalence of some psychiatric disorders (Hibbeln, 1998;Hibbeln, 2002;Noaghiul and Hibbeln, 2003) and on cross-sectional, case control or cohort studies investigating associations between these disorders and fish or n-3 polyunsaturated fatty acids (PUFAs) intake or tissue PUFAs concentrations (Alessandri et al, 2004;Freeman et al, 2006;Young et al, 2005). These studies are observational and do not constitute absolute proof that fish or n-3 PUFAs affect behavior.…”
Section: Introductionmentioning
confidence: 99%
“…48 Omega-3 fatty acids are also believed to reduce oxidative stress, possibly through their ability to increase the activity of certain antioxidant enzymes, including xanthine oxidase and superoxide dismutase. 49 Prior studies have found that supplementation with omega-3 fatty acids reduces the level of F2-isoprostanes, which is a marker of oxidant stress. 49 Omega-3 fatty acids may therefore be considered as a potential treatment in children with elevated markers of oxidative stress.…”
Section: Inflammatory Markers: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…49 Prior studies have found that supplementation with omega-3 fatty acids reduces the level of F2-isoprostanes, which is a marker of oxidant stress. 49 Omega-3 fatty acids may therefore be considered as a potential treatment in children with elevated markers of oxidative stress. If omega-3 fatty acids have a true beneficial effect on hyperactivity, it is also possible that this effect might be mediated through a change in the fatty acid levels in plasma or tissue.…”
Section: Inflammatory Markers: Omega-3 Fatty Acidsmentioning
confidence: 99%